Sustained high expression of human FVII following AAV8-mediated gene delivery in mice - Andrea D’Amico; Bas Blits; Joëlle van den Herik; Fred de Winter; Paul H.P. Kaijen; Barbara Hobo; Alexander Henrik van Asbeck; Joost Verhaagen; David G.M. Mosmuller; Jan Voorberg (Molecular Therapy: Methods & Clinical Development, 2025)
Factor VII (FVII) deficiency is a rare bleeding disorder with a prevalence of approximately 1:300,000–500,000 individuals. We explored whether adeno-associated virus (AAV)-mediated gene therapy can achieve durable and functional expression of human FVII (hFVII) in vivo. Wild-type hFVII (hFVIIwt) and a naturally occurring splice variant designated hFVII(-22) (GenBank: NM_019616.4) were expressed under the control of the Apolipoprotein E-derived hepatic locus control region and the α1-anti-trypsin promoter. Expression cassettes were packaged in either recombinant AAV5 (rAAV5) or recombinant AAV8 (rAAV8). For both hFVIIwt and hFVII(-22), 5- to 20-fold higher plasma levels of hFVII could be obtained when rAAV8 was used as a vector as opposed to rAAV5. Interestingly, hFVII levels obtained by employing rAAV8 expressing the hFVII(-22) cDNA variant were approximately 10 times higher than those obtained using rAAV8 expressing hFVIIwt. Based on these results, we generated an rAAV8-based gene therapy vector encoding hFVII(-22) and evaluated long-term expression in vivo. Employing a vector dose of 0.8 × 1012 genome copies (gc)/kg, we observed 48 weeks of functional hFVII expression which peaked at 16 IU/mL and stabilized at 7 IU/mL. These results support the pre-clinical development of AAV8-mediated delivery employing the splice-variant hFVII(-22) for patients suffering from FVII deficiency.